Gas−sensing properties of In2O3−Ga2O3 alloy films - Nikolaev, Vladimir I.; Almaev, Aleksei V.; Kushnarev, Bogdan O.; Pechnikov, Aleksei I.; Stepanov, Sergey I.; Chikiryaka, Andrei V.; Timashov, R. B.; Scheglov, Mikhail P.; Butenko, Pavel N.; Chernikov, Evgeniy V. (Technical physics letters)
The effect of the gaseous medium composition on the electrically conductive properties of In2O3−Ga2O3 films obtained by halide vapor phase epitaxy has been studied. In the temperature range of 100−550◦C, the In2O3−Ga2O3 films exhibit high sensitivity to H2, NH3 and possess hyphen performance and low base resistance. A qualitative mechanism for the sensitivity of In2O3−Ga2O3 films to gases is proposed.